Unblocking fluency: The power of pairwork, group discussion, and presentation in boosting speaking skills - Behnam Behforouz; Ali Al Ghaithi (Peoples' Friendship University of Russia (RUDN University), 2024)
This study attempts to measure the three commonly used techniques: pairwork, group discussion, and presentation in speaking classes. In addition, it compared the techniques to find out which leads to better performance of students in speaking skills. To collect the required data, 48 Omani undergraduates were randomly assigned to three experimental and one control group, with 12 students each. To ensure similar speaking proficiency levels, pre-tests of speaking were conducted. During the treatment period, experimental group A engaged in pairwork activities to achieve the speaking tasks, experimental group B was exposed to the presentation preparations, and experimental group C was allowed to work on group discussion activities. The control group followed the in-class instruction similar to experimental groups but without conscious engagement in any specific technique. After two weeks of the treatment, post-tests of speaking were conducted. The results revealed that the group mainly focused on the pairwork achieved significantly better than the other groups. The presentation group was in second place regarding better speaking skills performance. Although the experimental group C (group discussion) and the control group showed slight progress in the post-test, their performance was insignificant. The findings of the study are insightful for teachers and students.